Penerapan Overall Equipment Effectiveness (OEE) dan Reliability Centered Maintenance (RCM) dalam Meminimalkan Downtime Produksi Furnitur Ekspor - Muhammad Alhafizh Yahya; Herlina Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT. XYZ is an export furniture manufacturing company experiencing recurring downtime on Panel Saw and Spindle machines during July–December 2025, resulting in delays in product delivery. This study aims to measure machine effectiveness using the Overall Equipment Effectiveness (OEE) method and determine critical components through Reliability Centered Maintenance (RCM) based on Failure Mode and Effect Analysis (FMEA). The results show that the OEE values of the Panel Saw and Spindle machines are 84.3% and 88.3%, respectively. The dominant losses are caused by reduced speed losses and equipment failure. RCM analysis identifies v-belt and bearing components as critical components with the highest Risk Priority Number (RPN). The preventive maintenance strategy designed based on MTBF and MTTR values is expected to reduce downtime, improve machine availability, and minimize delays in export product delivery.